a) f(x)= 2(x – 3)² b) b) g(x) = -(x + 5)² me ajuda pfv
Soluções para a tarefa
Respondido por
2
Resposta:
(x – 3)² + (x + 5)² = 2 (x² + 23)
x² - 6x +9 + x² + 10x + 25 = 2 (x² + 23)
2x² + 4x + 34 = 2 ( x² + 23)
x² + 2x + 17 = x² + 23
x² + 2x+ 17 - x² - 23= 0
2x - 6 = 0
x - 3 = 0
x= 3
4.3 espero ter ajudado
muriloribeiro2004:
ajuda de mais mano muto obg
Respondido por
1
a) f(x) = 2.(x - 3)^2 ⇒ 2.(x-3).(x-3) ⇒ 2.(x.x - 3x - 3x - 3.-3) ⇒ 2.(x^2 - 6x +9) ⇒ 2x^2 - 12x + 18
b) - (x + 5)^2 ⇒ - (x+5).(x+5) ⇒ - (x.x + 5.x + 5.x + 25) ⇒ -x^2 - 10x - 25
Perguntas interessantes
Ed. Física,
9 meses atrás
Inglês,
9 meses atrás
Ed. Física,
9 meses atrás
Matemática,
1 ano atrás
Contabilidade,
1 ano atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás
Biologia,
1 ano atrás